IMPORTANCE OF WRITING SKILLS FOR PRIMARY EDUCATION - Nosirova Ruxshona Asliddin qizi; Razzaqova Shahlo Baxtiyor qizi (TADQIQOTLAR, 2025)
Abstract:Writing skills are a fundamental component of primary education, forming the basis for students’ future academic and personal development. At the early stages of learning, writing helps children organize their thoughts, improve hand–eye coordination, and develop essential language abilities such as vocabulary, grammar, and sentence structure. Strong writing skills also support reading comprehension, critical thinking, and effective communication. Furthermore, early exposure to writing encourages creativity and allows young learners to express their emotions, ideas, and experiences more confidently. As education becomes increasingly digital, writing remains a vital tool for learning across subjects and for building lifelong literacy. Therefore, strengthening writing instruction in primary schools is essential for ensuring students’ long-term educational success.